Investments and portfolio performance - Elton, Edwin J. (World Scientific, 2011)
This book contains the recent contributions of Edwin J. Elton and Martin J. Gruber to the field of investments. All of the articles in this book have been published in the leading finance and economic journals. Sixteen of the twenty articles have been published in the last ten years. This book supplements the earlier contributions of the editors published by MIT Press in 1999.